2012
DOI: 10.1159/000338343
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the AMH Type II Receptor in Two Extended Families with Persistent Müllerian Duct Syndrome: Lack of Phenotype/Genotype Correlation

Abstract: Our goal was to compare phenotype and genotype in two extended Middle-Eastern families affected by persistent Müllerian duct syndrome due to mutations of the type II anti-Müllerian hormone receptor (AMHR-II). The first, consanguineous, family consisted of 6 boys and 2 girls, the second consisted of 4 girls and 2 boys. In family I, 4 boys and 1 girl were homozygous for a stop mutation in the 9th exon of AMHR-II, removing part of the intracellular domain of the protein. In family II, 1 girl and 1 boy were homozy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 45 publications
0
23
0
2
Order By: Relevance
“…Accordingly, a similarly alternatively spliced AMHRII that is naturally expressed in rabbits does not bind ligand (di Clemente et al, 1994). In contrast to the constitutive cleavage of AMHRII, Alk5 (also known as TGFBR1; Liu et al, 2009;Mu et al, 2011), Alk3, Alk6 and BMPRII (Abdulhussein et al, 2008;Abduljabbar et al, 2012) were shown to undergo cleavage following phorbol ester stimulation, demonstrating that signaling by TGFb-SF receptors can also be dampened by inducible cleavage events.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a similarly alternatively spliced AMHRII that is naturally expressed in rabbits does not bind ligand (di Clemente et al, 1994). In contrast to the constitutive cleavage of AMHRII, Alk5 (also known as TGFBR1; Liu et al, 2009;Mu et al, 2011), Alk3, Alk6 and BMPRII (Abdulhussein et al, 2008;Abduljabbar et al, 2012) were shown to undergo cleavage following phorbol ester stimulation, demonstrating that signaling by TGFb-SF receptors can also be dampened by inducible cleavage events.…”
Section: Discussionmentioning
confidence: 99%
“…The latter, a A>G change at the penultimate base of the intron 2, was found in 3 unrelated Brazilian patients and may represent a founder effect [Nishi et al, 2012]. Similarly, the 4 families affected by mutation c.301G>A, p.(Gly101Arg) all originate from the Middle East or Pakistan [Abduljabbar et al, 2012]. The 5 families affected by mutation c.500A>G, p.(Tyr167Cys) are Northern European.…”
Section: Amh Gene Mutationsmentioning
confidence: 97%
“…2 ). The position of the testes/müllerian duct complex in PMDS may differ between brothers with the same genotype [Knebelmann et al, 1990;Abduljabbar et al, 2012;Nalbantoglu et al, 2015]. In patients described in the literature in whom molecular analysis has not been performed, the proportions are not very different: 41% for bilateral cryptorchidism, 32% for hernia uteri inguinalis , and 27% for transverse testicular ectopia.…”
Section: Position Of the Testesmentioning
confidence: 99%
See 1 more Smart Citation
“…AMHR2 gene mutations are located in the long arm 13.13 (12q.13.13) region of the 12 th chromosome. AMHR2 contains 11 exons and more than 27 mutations have already been described in this gene (14,15). The AMHR2 gene contains four intronic polymorphisms, located in t276a intron 1, c1280t intron 3, c1827t intron 5, and a6503g intron 10 (16).…”
Section: Discussionmentioning
confidence: 99%